Educational Health Disparities in Cardiovascular Disease Risk Factors: Findings from Jamaica Health and Lifestyle Survey 2007–2008 - Ferguson, Trevor S.; Younger-Coleman, Novie O. M.; Tulloch-Reid, Marshall K.; Hambleton, Ian R.; Francis, Damian K.; Bennett, Nadia R.; McFarlane, Shelly R.; Bidulescu, Aurelian; MacLeish, Marlene Y.; Hennis, Anselm J. M.; Wilks, Rainford J.; Harris, E. Nigel; et al. (Frontiers in Cardiovascular Medicine, 2017)
Objectives: Socioeconomic disparities in health have emerged as an important area in public health, but studies from Afro-Caribbean populations are uncommon. In this study, we report on educational health disparities in cardiovascular disease (CVD) risk factors, (hypertension, diabetes mellitus, hypercholesterolemia, and obesity), among Jamaican adults. Methods: We analysed data from the Jamaica Health and Lifestyle Survey 2007-08. Trained research staff administered questionnaires and obtained measurements of blood pressure, anthropometrics, glucose and cholesterol. CVD risk factors were defined by internationally accepted cut-points. Educational level was classified as primary or lower, junior secondary, full secondary and post-secondary. Educational disparities were assessed using age-adjusted or age-specific prevalence ratios and prevalence differences obtained from Poisson regression models. Post-secondary education was used as the reference category for all comparisons. Analyses were weighted for complex survey design to yield nationally representative estimates. Results: The sample included 678 men and 1553 women with mean age of 39.4 years. The effect of education on CVD risk factors differed between men and women and by age-group among women. Age-adjusted prevalence of diabetes mellitus was higher among men with less education, with prevalence differences ranging from 6.9 to 7.4 percentage points (p<0.05 for each group). Prevalence ratios for diabetes among men ranged from 3.3 to 3.5, but were not statistically significant. Age-specific prevalence of hypertension was generally higher among the less educated women, with statistically significant prevalence differences ranging from 6.0 to 45.6 percentage points and prevalence ratios ranging from 2.5 to 4.3. Similarly, estimates for obesity and hypercholesterolemia suggested that prevalence was higher among the less educated younger women (25-39 years), and among more educated older women (40-59 and 60-74 years). There were no statistically significant associations for diabetes among women, or for hypertension, high cholesterol or obesity among men. Conclusion: Educational health disparities were demonstrated for diabetes mellitus among men, and for obesity, hypertension and hypercholesterolemia among women in Jamaica. Prevalence of diabetes was higher among less educated men, while among younger women the prevalence of hypertension, hypercholesterolemia and obesity was higher among those with less education.